Positive electrode active material and method for manufacturing positive electrode active material

By using a large particle with high content of Ni, Y and Zr in the positive electrode active material of lithium-ion rechargeable batteries and coating Co on the surface of the particles, the problem of high DCR in the battery is solved, and the electrochemical performance and the cycle life are improved.

CN119968717APending Publication Date: 2025-05-09UMICORE(BE)
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380072359.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-10-25
Filing Date
2023-10-25
Publication Date
2025-05-09

AI Technical Summary

Technical Problem

The prior art is difficult to reduce the direct current resistance (DCR) of Ni-rich positive electrode active materials containing Y and Zr in lithium-ion rechargeable batteries, while improving electrochemical performance to extend cycle life.

Method used

An integral particle positive electrode active material containing more than 80 at% Ni, Y and Zr and coated with Co on the surface of the particles is used. A specific manufacturing method includes mixing, heating, grinding and reheating steps to form a particle structure with a Co edge/Co center ratio greater than 1.10.

Benefits of technology

The extended cycle life and reduced DCR of lithium-ion rechargeable batteries are achieved, improving the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119968717A_ABST
    Figure CN119968717A_ABST
Patent Text Reader

Abstract

The present invention relates to a positive electrode active material for a lithium ion rechargeable battery, the positive electrode active material comprising particles having Li, M 'and oxygen, where M' comprises: Ni in an amount x, where x > = 80 at% with respect to M '; co in an amount y, with respect to M ', 0.01 at% < = y < = 20.0 at%; mn in an amount z, where 0 at% < = z < = 20.0 at% with respect to M '; y in an amount b, where 0.01 at% < = b < = 2.0 at% with respect to M '; zr in an amount of c, where 0.01 at% < = c < = 2.0 at% with respect to M '; d in an amount a, where 0 at% < = a < = 5.0 at% with respect to M ', where D is at least one element selected from the list of B, Ba, Ca, Cr, Fe, Mg, Mo, Nb, S, Si, Sr, Ti, V, W, and Zn; wherein x, y, z, a, b and c are measured by ICR, where x + y + z + a + b + c is 100.0 at%, where the positive electrode active material comprises an integral particle, where the particle has a Co content measured by cross-sectional EDS (CS-EDS) at the edge of the particle, Co edge, where Co edge represents at% relative to the sum of the Ni, Mn and Co content measured by CS-EDS at the edge of the particle, where x + y + z + a + b + c represents at% relative to the sum of the Ni, Mn and Co content measured by CS-EDS, and where x + y + z + a + b + c represents at% relative to the sum of the Ni, Mn and Co content measured by CS-EDS at the edge of the particle. Wherein the particle has a Co content, Co center, measured by CS-EDS at the center of the particle, where Co center represents at% relative to the sum of the Ni, Mn and Co content measured by CS-EDS at the center of the particle, and where the ratio Co edge / Co center gt; and 1.10.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Technical Field and Background Art

[0002] The present invention relates to a positive electrode active material for a lithium ion rechargeable battery. More specifically, the present invention relates to a positive electrode active material comprising a monolithic particle having lithium (Li), M' and oxygen, wherein M' comprises more than 80 at% of nickel (Ni), yttrium (Y) and zirconium (Zr), and the particle is coated with cobalt (Co). The present invention also relates to a method for manufacturing the positive electrode active material, a battery comprising the positive electrode active material, and use of the battery comprising the positive electrode active material in an electric vehicle or a hybrid electric vehicle.

[0003] Meiling Zhang et al., Journal of Alloys and Compounds, 774, 2019, 82-89 reported that Ni-rich (i.e., containing more than 80 at% Ni) positive electrode active materials containing Y exhibited significantly enhanced cycling performance at a high voltage of 4.5 V. Chul-Ho Jung et al., J. Mater. Chem. A, 2021, 9, 17415–17424 also reported that Ni-rich positive electrode active materials containing Zr exhibited enhanced electrochemical performance by alleviating most degradation factors. CN113871603A discloses a positive electrode active material, which is prepared by heating a mixture of yttrium oxide, zirconium oxide, lithium hydroxide and a precursor containing Ni, Mn and Co, and comprises polycrystalline particles. Although Ni-rich positive electrode active materials containing Y and Zr show enhancement in specific electrochemical properties of lithium-ion rechargeable batteries, methods for reducing the direct current resistance (DCR) of lithium-ion rechargeable batteries containing Ni-rich positive electrode active materials having Y and Zr are unknown. Therefore, there is a need for a Ni-rich positive electrode active material containing Y and Zr, which has a reduced DCR and enhanced electrochemical properties such as an extended cycle life.

[0004] A first object of the present invention is to provide a positive electrode active material comprising Y and Zr, wherein a lithium ion rechargeable battery comprising the positive electrode active material has improved electrochemical properties, such as an extended cycle life and a reduced DCR.

[0005] A second object of the present invention is to provide a method for producing a positive electrode active material containing Y and Zr.

[0006] A third object of the present invention is to provide a battery comprising the positive electrode active material.

[0007] A fourth object of the present invention is to provide use of the battery comprising the positive electrode active material in an electric vehicle or a hybrid electric vehicle. Summary of the invention

[0008] The first object is achieved by providing a positive electrode active material for a lithium ion rechargeable battery, wherein the positive electrode active material comprises particles having Li, M' and oxygen, wherein M' comprises:

[0009] −Ni with content x, where x ≥ 80 at% relative to M';

[0010] −Co with content y, where 0.01 at%≤ y ≤ 20.0 at% relative to M';

[0011] − Mn with content z, where 0 at% ≤ z ≤ 20.0 at% relative to M';

[0012] − Y with a content b, where 0.01 at% ≤ b ≤ 2.0 at% relative to M';

[0013] − Zr with a content of c, where 0.01 at% ≤ c ≤ 2.0 at% relative to M';

[0014] − D in an amount a, wherein 0 at% ≤ a ≤ 5.0 at% relative to M', wherein D is at least one element selected from the following list: Al, B, Ba, Ca, Cr, Fe, Mg, Mo, Nb, S, Si, Sr, Ti, V, W and Zn;

[0015] where x, y, z, a, b and c are measured by ICP,

[0016] where x+y+z+a+b+c is 100.0 at%.

[0017] wherein the positive electrode active material comprises monolithic particles,

[0018] The particles have a Co content Co measured by cross-sectional EDS (CS-EDS) at the edge of the particles. 边缘 , where Co 边缘 Expressed as at% relative to the sum of Ni, Mn and Co contents measured by CS-EDS at the edge of the particle

[0019] The particles have a Co content Co measured by CS-EDS at the center of the particle. 中心 , where Co 中心 expressed as at% relative to the sum of the Ni, Mn and Co contents measured by CS-EDS at the center of the particle, and

[0020] The ratio Co 边缘 / Co 中心 > 1.10.

[0021] The second object is achieved by providing a method for producing the positive electrode active material, the method comprising the following consecutive steps:

[0022] a. mixing a precursor comprising Ni and optionally one or both of Co and Mn with a Y source, a Zr source, a Li source, and optionally a D source to obtain a first mixture, wherein D is at least one element selected from the following list: Al, Ba, Ca, Cr, Fe, Mg, Mo, Nb, S, Si, Sr, Ti, V, W, and Zn,

[0023] b. heating the first mixture at a temperature between 650°C and 1000°C to obtain a first heated material,

[0024] c. grinding the first heated material to obtain a ground powder,

[0025] d. mixing the ground powder with a Co source to obtain a second mixture,

[0026] e. heating the second mixture at a temperature between 500° C. and 900° C. to obtain the positive electrode active material.

[0027] The third object is achieved by providing a battery including the positive electrode active material.

[0028] The fourth object is to provide use of the battery comprising the positive electrode active material in an electric vehicle or a hybrid electric vehicle.

[0029] The positive electrode active material according to the present invention has an extended cycle life and a reduced DCR when used in a lithium ion rechargeable battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 is a graph showing the cycle life of CEX1.1, CEX1.2 and EX1 at 45°C.

[0031] Figure 2 is a graph showing the cycle life of CEX2.1, CEX2.2, CEX2.3, EX2.1 and EX2.2 at 45°C.

[0032] Figure 3 is a graph showing the DCR of CEX1.1, CEX1.2 and EX1 at 45°C.

[0033] Figure 4is a graph showing the DCR of CEX2.1, CEX2.2, CEX2.3, EX2.1 and EX2.2 at 45°C.

[0034] Figure 5 is a SEM image of EX1.

[0035] Figure 6 is a cross-sectional SEM image of EX1, where A is the location of the particle center where Co is measured. 中心 , and B is the location of the particle edge where Co is measured 边缘 . DETAILED DESCRIPTION

[0036] In the following specific embodiments, preferred embodiments are described in detail to practice the present invention. Although the present invention is described with reference to these specific preferred embodiments, it should be understood that the present invention is not limited to these preferred embodiments. In contrast, the present invention includes many substitutions, modifications and equivalent forms, which will become apparent by considering the following specific embodiments.

[0037] Positive electrode active material

[0038] In a first aspect, the invention relates to a positive electrode active material for a lithium ion rechargeable battery, the positive electrode active material comprising particles having Li, M' and oxygen, wherein M' comprises:

[0039] −Ni with content x, where x ≥ 80 at% relative to M';

[0040] −Co with content y, where 0.01 at%≤ y ≤ 20.0 at% relative to M';

[0041] − Mn with content z, where 0 at% ≤ z ≤ 20.0 at% relative to M';

[0042] − Y with a content b, where 0.01 at% ≤ b ≤ 2.0 at% relative to M';

[0043] − Zr with a content of c, where 0.01 at% ≤ c ≤ 2.0 at% relative to M';

[0044] − a content of D, wherein 0 at% ≤ a ≤ 5.0 at% relative to M', wherein D is at least one element selected from the following list: Al, B, Ba, Ca, Cr, Fe, Mg, Mo, Nb, S, Si, Sr, Ti, V, W and Zn;

[0045] where x, y, z, a, b and c are measured by ICP,

[0046] where x+y+z+a+b+c is 100.0 at%.

[0047] wherein the positive electrode active material comprises monolithic particles,

[0048] The particles have a Co content Co measured by cross-sectional EDS (CS-EDS) at the edge of the particles. 边缘 , where Co 边缘 Expressed as at% relative to the sum of Ni, Mn and Co contents measured by CS-EDS at the edge of the particle

[0049] The particles have a Co content Co measured by CS-EDS at the center of the particle. 中心 , where Co 中心 expressed as at% relative to the sum of the Ni, Mn and Co contents measured by CS-EDS at the center of the particle, and

[0050] The ratio Co 边缘 / Co 中心 > 1.10.

[0051] In the framework of the present invention, the edge of a particle is the boundary or outer limit that distinguishes the particle from its external environment. The center of a particle is the midpoint of the line that is the longest of the lines connecting two points on the edge of the particle.

[0052] In the framework of the present invention, at% means atomic percentage.At% or "atomic percentage" of a given element means the percentage of atoms of said element to all atoms in the claimed composition.

[0053] ICP-OES provides the weight percentage (wt%) of each element contained in the material whose composition is determined by this technique. The conversion from wt% to at% is as follows: at% of the first element E1 in the material (E at1 ) can be obtained by applying the following formula from a given wt% of the first element E1 in the material (E wt1 ) Conversion:

[0054] ,

[0055] Where E aw1 is the standard atomic weight of the first element E1, E wti is the i-th element E i wt%,E awi is the i-th element E iThe standard atomic weight of the material, and n is an integer representing the number of types of all elements contained in the material.

[0056] The present inventors have found that an extended cycle life and a reduced DCR of a lithium ion rechargeable battery are achieved by a positive electrode active material according to the present invention. In detail, the present inventors have found that a lithium ion rechargeable battery comprising a positive electrode active material according to the present invention has an extended cycle life and a reduced DCR, wherein the material comprises more than 80 at % Ni, wherein Y and Zr are added, wherein the whole particle is included, and wherein the ratio Co 边缘 / Co 中心 > 1.10.

[0057] In the framework of the present invention, "monolithic" particles are particles each containing only one primary particle, as observed in a SEM image.

[0058] Even when operated under extreme conditions, the monolithic particles can maintain their morphological integrity, and therefore, the contact area between the electrolyte and the monolithic particles is reduced due to the generation of microcracks compared to polycrystalline particles. The reduction in contact area reduces the gas release caused by additional side reactions between the electrolyte and the monolithic particles and also reduces the DCR.

[0059] In a particularly preferred embodiment, the positive electrode active material according to the present invention is a powder comprising single particles and / or secondary particles, wherein each particle in the single particle consists of only one primary particle, and each secondary particle in the secondary particles consists of at least two primary particles and at most twenty primary particles, as observed in the SEM image. Preferably, at least 30% of the particles constituting the powder observed in the SEM image, more preferably at least 50% of the particles are single particles and / or secondary particles. The number of primary particles constituting the single particles and / or secondary particles is at least 45µm x at least 60µm (i.e., at least 2700µm 2 ), preferably: at least 100µm x 100µm (i.e. at least 10000µm 2 ). The particles in the image should be evenly distributed, avoiding overlap between particles. This can be achieved by pouring a small amount of the powder sample into an adhesive attached to the SEM sample holder and blowing air to remove excess powder. In the context of the present invention, primary particles are distinguished from each other in the SEM image by observing the grain boundaries between the primary particles. A grain boundary is defined as an interface between two primary particles, preferably where the atomic planes of the two primary particles are aligned in different orientations and meet as a crystallographic discontinuity.

[0060] In a preferred embodiment, Co 边缘 / Co中心 It may be greater than 1.50, preferably greater than 1.65, more preferably greater than 1.80.

[0061] In a preferred embodiment, x may be 85 at% or more, preferably 86.5 at% or more, more preferably 88 at% or more.

[0062] In a preferred embodiment, x may be less than 98.5 at%, preferably less than 96 at%, more preferably less than 94 at%.

[0063] In a preferred embodiment, (y+z) may be greater than 1.0 at %, preferably greater than 3.0 at %, more preferably greater than 5.0 at %.

[0064] In a preferred embodiment, b may be 0.02 at % or more, preferably 0.03 at % or more, more preferably 0.04 at % or more.

[0065] In a preferred embodiment, b may be 2.0 at% or less, preferably 1.0 at% or less, more preferably 0.5 at% or less.

[0066] In a preferred embodiment, c may be 0.08 at % or more, preferably 0.10 at % or more, more preferably 0.12 at % or more.

[0067] In a preferred embodiment, c may be 2.0 at% or less, preferably 1.0 at% or less, more preferably 0.5 at% or less.

[0068] In a preferred embodiment, the median particle size D50 may be at least 2.0 μm and at most 15.0 μm, as determined by laser diffraction particle size analysis.

[0069] In a preferred embodiment, D is a content a wherein 0 at% ≤ a ≤ 5.0 at%, relative to M', preferably wherein 0 at% ≤ a ≤ 2.0 at%, relative to M', more preferably wherein 0 at% ≤ a ≤ 1.0 at%, most preferably a is about 0.

[0070] In a preferred embodiment, D is at least one element selected from the following list: Al, B, Mo, Nb, Sr, Ti, V, W and Zn; preferably, D is at least one element selected from the list of Al, B, Nb, Sr, Ti and W. In a particularly preferred embodiment, D is Al.

[0071] Method for producing positive electrode active material

[0072] In a second aspect, the invention relates to a method for producing a positive electrode active material according to the first aspect, the method comprising the following consecutive steps:

[0073] a. mixing a precursor comprising Ni and optionally one or both of Co and Mn with a Y source, a Zr source, a Li source, and optionally a D source to obtain a first mixture, wherein D is at least one element selected from the following list: Al, Ba, Ca, Cr, Fe, Mg, Mo, Nb, S, Si, Sr, Ti, V, W, and Zn

[0074] b. heating the first mixture at a temperature between 650°C and 1000°C to obtain a first heated material,

[0075] c. grinding the first heated material to obtain a ground powder,

[0076] d. mixing the ground powder with a Co source to obtain a second mixture,

[0077] e. heating the second mixture at a temperature between 500° C. and 900° C. to obtain the positive electrode active material.

[0078] The positive electrode active material manufactured by the method according to the second aspect comprises integral particles. The temperature of the step of heating the first mixture is high enough to promote the growth of primary particles in the first heated material. Then, the first heated material is ground to form integral particles. Preferably, the grinding is wet bead milling.

[0079] In a preferred embodiment, the Y source may be at least one selected from yttrium oxide and yttrium zirconium oxide compounds. The yttrium oxide may be Y2O3, and the yttrium zirconium oxide may be Y 0.3 Zr 0.7 O 1.85 .

[0080] In a preferred embodiment, the Zr source may be at least one selected from the group consisting of zirconium oxide, lithium zirconium oxide, and yttrium zirconium oxide compounds. The zirconium oxide may be ZrO2, the lithium zirconium oxide may be Li2ZrO3, and the yttrium zirconium oxide may be Y 0.3 Zr 0.7 O 1.85 .

[0081] In a preferred embodiment, both the Y source and the Zr source may be yttrium zirconium oxide compounds. 0.3 Zr 0.7 O 1.85 .

[0082] The inventors of the present invention have found that a lithium ion rechargeable battery including a positive electrode active material manufactured by using yttria zirconium oxide as a Y source and a Zr source during step a of mixing precursors has a longer cycle life and a lower DCR than a lithium ion rechargeable battery including a positive electrode active material manufactured by using zirconium oxide and / or lithium zirconium oxide as a Zr source and yttrium oxide as a Y source during step a of mixing precursors.

[0083] In a preferred embodiment, the first heated material obtained during step b of heating the first mixture may be mixed in an aqueous solution comprising Co by using wet bead milling.

[0084] Battery

[0085] In a third aspect, the invention relates to a battery comprising the positive electrode active material according to the first aspect.

[0086] Battery Purpose

[0087] In a fourth aspect, the invention relates to the use of a battery according to the third aspect.

[0088] As recognized by those skilled in the art, all embodiments directed to the positive electrode active material according to the first aspect are applicable mutatis mutandis to the second, third and fourth aspects.

[0089] Experimental Tests Used in the Examples

[0090] The following analytical methods were used in the examples:

[0091] A) Particle size distribution (PSD) analysis

[0092] After dispersing the examples of the positive electrode active material powders as described below in an aqueous medium, the PSD was measured using a Malvern Mastersizer 3000 equipped with a Hydro MV wet dispersion accessory. In order to improve the dispersibility of the positive electrode active material powder examples, sufficient ultrasonic irradiation and stirring were applied, and appropriate surfactants were introduced. D50 was defined as the particle size at 50% of the cumulative volume % distribution.

[0093] B) Inductively Coupled Plasma – Optical Emission Analyzer (ICP-OES)

[0094] The content of the metal in the positive electrode active material example as described below is measured by inductively coupled plasma-emission spectrometry (ICP-OES) method using Agillent ICP 720-OES. A 1 gram powder sample of each example was dissolved in 50 mL of high purity hydrochloric acid in a conical flask. The bottle was covered with a watch glass and heated on a hot plate at 380 ° C until the sample was completely dissolved. After cooling to room temperature, the solution and rinse water of the conical flask were transferred to a 250 mL volumetric flask. After that, the volumetric flask was filled with deionized water until the 250 mL mark and then completely homogenized. An appropriate amount of solution was taken out by pipette and transferred to a 250 mL volumetric flask for the second dilution, at which time the internal standard and 10% hydrochloric acid were filled in the volumetric flask until the 250 mL mark and then homogenized. Finally, the solution was used for ICP-OES measurement. The content of Ni, Mn, Co, Y and Zr is expressed as the wt% of the total amount of these contents.

[0095] C) Cross-sectional energy dispersive X-ray spectroscopy (CS-EDS)

[0096] C1) Cross-section preparation

[0097] Cross sections of the positive electrode active material examples described below were prepared by an ion beam cross section polisher (CP) instrument JEOL (IB-19530CP) The instrument used argon as the beam source.

[0098] To prepare the specimen, a small amount of positive electrode active material powder was mixed with a resin and a hardener, and the mixture was then heated on a hot plate for 10 minutes. After heating, it was placed in an ion beam instrument for cutting and set to a 3-hour duration at a voltage setting of 6.5 kV in a standard program.

[0099] C2) Energy Dispersive X-ray Spectroscopy (EDS) Analysis

[0100] Using the examples of positive electrode active materials prepared according to the above method C1), the concentrations of Ni, Mn and Co from the edge to the center of the positive electrode active material particles were analyzed by energy dispersive X-ray spectroscopy (EDS). Particles with a diameter of about the D50 value measured by PSD according to section A) were selected for each example in the analysis of the examples. EDS was performed by a 50 mm X-ray diffraction analyzer equipped with a 50 mm X-ray diffraction analyzer from Oxford instruments. 2 The X-MaxN EDS sensor was used to perform the analysis on a JEOL JSM 7100F SEM device. EDS analysis of the positive electrode active material particles provides quantitative elemental analysis of the cross section, assuming that the particles are spherical. A straight line was set from the edge to the center point of the particle, and the Ni, Mn and Co concentrations were measured at the edge and center and expressed as at% relative to the sum of the Ni, Mn and Co contents at each point.

[0101] D) Full battery unit test

[0102] D1) Preparation of full battery cell

[0103] A 2000 mAh pouch cell was prepared as follows: a positive electrode active material powder, Super-P (Super-P, Imerys Graphite & Carbon) as a positive electrode conductor, and polyvinylidene fluoride (PVDF S5130, Solvay) as a positive electrode binder were added to N-methyl-2-pyrrolidone (NMP) as a dispersion medium, so that the mass ratio of the positive electrode active material powder, the positive electrode conductor (super P) and the positive electrode binder was set to 95 / 3 / 2. Thereafter, the mixture was kneaded to prepare a positive electrode mixture slurry. The resulting positive electrode mixture slurry was then applied to both sides of a positive electrode current collector made of 20µm thick aluminum foil. The width of the application area was 88.5 mm and the length was 425 mm. The typical load weight of the positive electrode active material is about 14.8±1 mg / cm 2 Then, the electrode was dried and rolled using a pressure of 4.5 MPa. In addition, an aluminum plate as a positive electrode current collector was arc welded to the end of the positive electrode.

[0104] A commercially available negative electrode was used. Briefly, a mixture of artificial graphite, carbon (Super P (Imerys)), sodium carboxymethyl cellulose, and styrene butadiene rubber in a mass ratio of 95.0 / 1 / 1.5 / 2.5 was applied to both sides of a copper foil. A nickel plate used as a negative electrode current collector was arc welded to the end of the negative electrode. The typical loading weight of the negative electrode active material was about 10±1 mg / cm 2 .

[0105] The non-aqueous electrolyte is obtained by dissolving lithium hexafluorophosphate (LiPF6) salt at a concentration of 1.2 mol / L in a mixed solvent of ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) in a volume ratio of 1:1:1. It contains 1.0 wt.% lithium difluorophosphate (LiPO2F2) and 1.0 wt.% vinylene carbonate (VC) as additives.

[0106] The positive electrode sheet, the negative electrode sheet, and the microporous polymer separator (13µm) sheet interposed between the positive electrode sheet and the negative electrode sheet were spirally wound using a winding mandrel to obtain a spirally wound electrode assembly. The assembly and the electrolyte were then placed in an aluminum laminate bag in an air-dried room with a dew point of -50°C to prepare a flat pouch lithium secondary battery. When charged to 4.20 V, the design capacity of the secondary battery was 2000 mAh. The full battery unit test procedure was defined using a 1 C current of 2000 mA / g.

[0107] D2) Cycle life test

[0108] A. Precharge and Formation

[0109] The nonaqueous electrolyte solution was immersed in the prepared dry storage battery at room temperature for 8 hours. The battery was precharged with a current of 0.25 C until it reached 14% of its theoretical capacity and aged for one day at room temperature. Then, the battery was degassed for 30 seconds using a pressure of -760 mmHg and the aluminum bag was sealed. During the measurement, the bag was assembled in a pressing fixture with a silicon pad.

[0110] The cell was charged in CC mode (constant current) at a current of 0.2 C up to 4.2 V, and charged in CV mode (constant voltage) until a cutoff current of C / 20 was reached. The cell was discharged in CC mode at a current of 0.2 C down to 2.7 V. The cell was then fully charged in CC mode at a current of 0.50 C up to 4.2 V, and charged in CV mode until a cutoff current of C / 20 was reached.

[0111] Thereafter, the cell was discharged in CC mode at a current of 0.50 C to as low as 2.7 V. The cell was again charged in CC mode at a current of 0.5 C up to 4.2 V and in CV mode until a cutoff current of C / 20 was reached. The final charging step was done at 25°C.

[0112] B. Cycle life test

[0113] The lithium secondary full cell batteries were continuously charged and discharged under the following conditions (at 45°C) to determine their charge-discharge cycle performance:

[0114] - Charge in CC mode at 1 C rate up to 4.2 V, then charge in CV mode until C / 20,

[0115] -Then let the battery rest for 10 minutes.

[0116] -Discharged at 1 C rate in CC mode down to 2.7 V,

[0117] -Then let the battery rest for 10 minutes.

[0118] - Charge-discharge cycling was performed until 600 cycles were performed. Every 100 cycles, discharge was performed in CC mode at 0.1 C rate down to 2.7 V.

[0119] The internal resistance or DC resistance (DCR) was measured at 1.5C for 10 s at the beginning of every 100 cycle repetitions and at the end of the 600th cycle.

[0120] Cycle life is defined as the number of charge-discharge cycles until the capacity drops to 80%.

[0121] E) FE-SEM analysis

[0122] The morphology of the materials was analyzed by scanning electron microscopy (SEM). The measurements were performed using a JEOL JSM 7100F SEM instrument under a high vacuum environment of 9.6x10-5 Pa at 25°C.

[0123] Example

[0124] The present invention is further illustrated in the following examples:

[0125] Comparative Example 1

[0126] The positive electrode active material CEX1.1 is prepared by a solid-state reaction between a lithium source and a transition metal-based source precursor according to the following steps:

[0127] 1. Coprecipitation: A coprecipitation process was used to prepare a metal composition of Ni in a large continuous stirred tank reactor (CSTR) with mixed nickel-manganese-cobalt sulfate, sodium hydroxide and ammonia. 0.90 Mn 0.05 Co 0.05 Transition metal oxide hydroxide precursors.

[0128] 2. First mixing: The precursor prepared from step 1) was mixed with LiOH in an industrial blender to obtain a first mixture having a lithium to metal ratio of 0.99.

[0129] 3. First heating: The mixture from step 2) was heated at a first temperature of 890° C. for 12 hours under oxygen flow to obtain a first heated material.

[0130] 4. Wet bead milling: The first heated material was bead milled in a solution containing 0.5 at% Co relative to the total molar content of Ni, Mn and Co in the first heated product, followed by a drying and sieving process to obtain a ground product. The bead milling solid to solution weight ratio was 10:7 and was performed for 50 minutes.

[0131] 5. Second mixing: The ground product from step 4) was mixed with 1.5 at% Co from nano Co oxide powder and 0.25 at% Zr from ZrO2 powder.

[0132] 6. Heat treatment: The second mixture from step 5) was heated at 770° C. for 12.5 hours under an oxygen atmosphere to obtain CEX1.1.

[0133] CEX1.2 was prepared according to the same method as CEX1.1, except that ZrO2 powder was added with Li in the first mixing to obtain a first mixture containing 0.25 at% Zr and a lithium metal ratio of 0.99, and ZrO2 was not added in the second mixing.

[0134] Example 1

[0135] EX1 was prepared according to the same method as CEX1.1, except that Y was added together with LiOH in the first mixing. 0.3 Zr 0.7 O 1.85 powder, thereby obtaining a first mixture containing 0.175 at % of Zr, 0.075 at % of Y and a lithium metal ratio of 0.99, and no ZrO 2 was added in the second mixture.

[0136] Comparative Example 2

[0137] The positive electrode active material CEX2.1 is prepared by a solid-state reaction between a lithium source and a transition metal-based source precursor according to the following steps:

[0138] 1. Coprecipitation: A coprecipitation process was used to prepare a metal composition of Ni in a large continuous stirred tank reactor (CSTR) with mixed nickel-manganese-cobalt sulfate, sodium hydroxide and ammonia. 0.96 Mn 0.01 Co 0.03 Transition metal oxide hydroxide precursors.

[0139] 2. First mixing: The precursor prepared from step 1) was mixed with LiOH, Al2O3 and ZrO2 in an industrial blender to obtain a first mixture having 700 ppm Al, 0.117 at% ZrO2, and a lithium metal ratio of 1.01.

[0140] 3. First heating: The mixture from step 2) was heated at a first temperature of 805° C. for 10 hours under oxygen flow, and then the temperature was reduced to a second temperature of 720° C. for 5 hours to obtain a first heated material.

[0141] 4. Wet bead milling: The first heated material was bead milled in a solution containing 0.5 at% Co relative to the total molar content of Ni, Mn and Co in the first heated product, followed by a drying and sieving process to obtain a ground product. The bead milling solid to solution weight ratio was 5:5 and was performed for 13 hours.

[0142] 5. Second mixing: The milled product from step 4) was mixed with LiOH to obtain a lithium to metal ratio of 0.99, 1.5 at% Co from nano Co oxide powder (Co3O4), 500 ppm Nb from Nb2O5 and 500 ppm Al from Al2O3 powder.

[0143] 6. Heat treatment: The second mixture from step 5) was heated at 710° C. for 12.5 hours under an oxygen atmosphere to obtain CEX2.1.

[0144] CEX2.2 was prepared according to the same method as CEX2.1, except that 0.025 at% Y2O3 was added together with LiOH and Al2O3 instead of ZrO2 powder in the first mixture.

[0145] CEX2.3 was prepared according to the same method as CEX2.1, except that (i) Y was added together with LiOH and Al2O3 in the first mixing. 0.3 Zr 0.7 O 1.85 powder instead of ZrO2 powder to obtain a first mixture containing 0.117 at% Zr, 0.050 at% Y and a lithium to metal ratio of 1.01, (ii) wet bead milling in water instead of Co solution, and (iii) no Co3O4 was added in the second mix.

[0146] Example 2

[0147] EX2.1 was prepared according to the same method as CEX2.1, except that Y was added together with LiOH and Al2O3 in the first mixing. 0.3Zr 0.7 O 1.85 powder instead of ZrO2 powder, thereby obtaining a first mixture containing 0.117 at% of Zr, 0.050 at% of Y and a lithium metal ratio of 0.99.

[0148] EX2.2 was prepared according to the same method as CEX2.1, except that 0.025 at% Y2O3 was added together with LiOH, Al2O3 and ZrO2 in the first mixing.

[0149] result

[0150]

[0151] Table 1 summarizes the compounds added in the first mixing, wet milling and second mixing except the precursor and Li source. CEX1.1 and CEX1.2 are positive electrode active materials containing Zr, while EX1 further contains Y. All particles in Table 1 are integral due to the first temperature during the first mixing and wet bead milling. Figure 5 is a SEM image of EX1. It is confirmed that each particle of EX1 contains only one primary particle, and therefore, each particle of EX1 is integral. The electrochemical characteristics of the full battery unit test prove that EX1 has a longer cycle life than CEX1.1 and CEX1.2 shown in Table 1, exceeding 2300 cycles at 80% capacity. Figure 1 Capacity versus cycle number is shown for CEX1.1, CEX1.2 and EX1 up to 500 cycles, and by Figure 1 The number of cycles at 80% capacity was calculated by linear extrapolation of the obtained data shown in . Figure 3 It is also shown that EX1 has lower DCR values ​​at 600 cycles compared to CEX1.1 and CEX1.2, showing the benefit of adding Y together with Zr during the first mixing.

[0152] CEX2.1, CEX2.2, EX2.1 and EX2.2 are positive electrode active materials, which differ from CEX1.1, CEX1.2 and EX1 in that the Ni content in CEX2.1, CEX2.2, EX2.1 and EX2.2 is about 93.6 at%, and CEX2.1, CEX2.2, EX2.1 and EX2.2 further contain Nb and Al. CEX2.1 does not contain Y and CEX2.2 does not contain Zr, while EX2.1 and EX2.2 contain both Y and Zr. CEX2.3 differs from EX2.1 in that: (i) the step of wet bead milling is carried out in water instead of in a solution containing Co, and (ii) Co3O4 is not added in the second mixing step. Therefore, compared with EX2.1, Co is not enriched on the edges of the particles of CEX2.3. Electrochemical characterization via full cell tests demonstrated that EX2.1 and EX2.2 had longer cycle life, exceeding 1200 cycles at 80% capacity, compared to CEX2.1, CEX2.2, and CEX2.3 as shown in Table 1. Figure 2 Capacity versus cycle number for CEX2.1, CEX2.2, EX2.1 and EX2.2 up to 500 cycles is shown, and by Figure 2 The number of cycles at 80% capacity was calculated by linear extrapolation of the obtained data shown in . Figure 4 It is also shown that EX2.1 and EX2.2 have lower DCR values ​​at 600 cycles compared to CEX2.1 and CEX2.2, showing the benefit of adding Y together with Zr during the first mixing period. Consistent with the results obtained from the comparison of EX1 with CEX1.2, both EX1.1 and EX1.2 exhibit improved electrochemical characteristics compared to CEX2.1 and CEX2.2.

[0153] The Y and Zr in the first mix can be added separately in two different sources (such as EX2.2) or added in a single source as a yttria zirconium compound (such as EX2.1). Compare the cycle life and DCR of EX2.1 with Figure 2 and Figure 4 Compared with the cycle life and DCR of EX2.2 shown in , the cycle life of EX2.1 is longer than that of EX2.2, and the DCR of EX2.1 is lower than that of EX2.2. This proves that when Y and Zr in the first mixture are added as a single source, the cycle life and DCR of the positive electrode active material according to the present invention are improved.

[0154] Table 2 presents the Ni, Mn and Co contents at the edge and center of the positive electrode active material particles of EX2.1 obtained from EDX of cross-sectional particles. 边缘 / Co 中心The ratio of exceeds 1.0, indicating that Co is enriched on the edge portion of the positive electrode active material particles. The edge enrichment of Co originates from the addition of the Co compound in the wet milling and the second mixing process.

[0155] It is concluded that the combination of Y, Zr and Co in the positive electrode active material as shown in EX1, EX2.1 and EX2.2 synergistically benefits the improved cycle life and reduced DCR value at 600 cycles.

Claims

1. A positive electrode active material for a lithium ion rechargeable battery, the positive electrode active material comprising Li, M' and oxygen, wherein M' comprises: −Ni with content x, where x ≥ 80 at% relative to M'; −Co with content y, where 0.01 at% ≤ y ≤ 20.0 at% relative to M'; − Mn with content z, where 0 at% ≤ z ≤ 20.0 at% relative to M'; − Y with a content b, where 0.01 at% ≤ b ≤ 2.0 at% relative to M'; − Zr with a content of c, where 0.01 at% ≤ c ≤ 2.0 at% relative to M'; − D in an amount a, wherein 0 at% ≤ a ≤ 5.0 at% relative to M', wherein D is at least one element selected from the group consisting of Al, Ba, Ca, Cr, Fe, Mg, Mo, Nb, S, Si, Sr, Ti, V, W and Zn; where x, y, z, a, b and c are measured by ICP, where x+y+z+a+b+c is 100.0 at%. wherein the positive electrode active material comprises monolithic particles, wherein the particle has a Co content Co measured by cross-sectional EDS (CS-EDS) at the edge of the particle 边缘 , where Co 边缘 Expressed as at % relative to the sum of the Ni, Mn and Co contents measured by CS-EDS at the edge of the particle wherein the particle has a Co content Co measured by CS-EDS at the center of the particle 中心 , where Co 中心 expressed as at% relative to the sum of the Ni, Mn and Co contents measured by CS-EDS at the center of the particle, and The ratio Co 边缘 / Co 中心 > 1.

10. 2 . The positive electrode active material according to claim 1 , wherein each of the monolithic particles contains only one primary particle.

3. The positive electrode active material according to claim 1 or 2, wherein Co 边缘 / Co 中心 > 1.

50.

4. The positive electrode active material according to any one of the preceding claims, wherein 85.0 at% ≤ x ≤ 98.5 at%, preferably 86.5 at% ≤ x ≤ 96.0 at%, more preferably 88.0 at% ≤ x ≤ 94.0 at%.

5. The positive electrode active material according to any one of the preceding claims, wherein (y+z) > 1.0 at%.

6. The positive electrode active material according to any one of the preceding claims, wherein b ≥ 0.02 at%.

7. The positive electrode active material according to any one of the preceding claims, wherein c ≥ 0.08 at%.

8. The positive electrode active material of any one of the preceding claims, wherein the particles have a median size D50 of at least 2.0 μm and at most 15.0 μm as determined by laser diffraction particle size analysis.

9. A method for producing a positive electrode active material according to any one of the preceding claims, the method comprising the following consecutive steps: a. mixing a precursor comprising Ni and optionally one or both of Co and Mn with a Y source, a Zr source, a Li source, and optionally a D source to obtain a first mixture, wherein D is at least one element selected from the group consisting of Al, Ba, Ca, Cr, Fe, Mg, Mo, Nb, S, Si, Sr, Ti, V, W, and Zn, b. heating the first mixture at a temperature between 650°C and 1000°C to obtain a first heated material, c. grinding the first heated material to obtain a ground powder, d. mixing the ground powder with a Co source to obtain a second mixture, e. heating the second mixture at a temperature between 500° C. and 900° C. to obtain the positive electrode active material. 10 . The method according to claim 9 , wherein the Y source is at least one selected from yttrium oxide and yttrium zirconium oxide compounds.

11. The method according to claim 9 or 10, wherein the Zr source is at least one selected from zirconium oxide, lithium zirconium oxide, and yttrium zirconium oxide compounds.

12. The method according to claim 9, wherein the Y source and the Zr source are yttria zirconium compounds. 13 . The method according to claim 9 , wherein the first heated material is mixed in an aqueous solution containing Co by using wet bead milling. 14 . A battery comprising the positive electrode active material according to claim 1 .

15. Use of the battery according to claim 14 in an electric vehicle or a hybrid electric vehicle.

Citation Information

Patent Citations

  • High-nickel ternary positive electrode material and preparation method thereof

    CN113871603A